Peran dan Tantangan Koperasi dalam Pembangunan Ekonomi Masyarakat yang Berada di Desa Namo Bintang Kecamatan Pancur Batu - Perkasa, Ripho Delzy; Sulistiani, Wiwid Nur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cooperatives play a crucial role in the economic development of communities, especially in rural areas like Desa Namo Bintang, Kecamatan Pancur Baru. Cooperatives can be an effective means to stimulate economic growth and improve the welfare of the community. However, in fulfilling their role, cooperatives face various challenges that need to be overcome in order to provide maximum benefits to the community. This research aims to analyze the role of cooperatives in the economic development of the community in Desa Namo Bintang and identify the challenges faced by cooperatives in achieving their goals. The research methodology employed in this study is field research, including interviews and direct observations of the cooperatives in Desa Namo Bintang. The research identifies several challenges faced by cooperatives in Desa Namo Bintang. Firstly, there is a limitation of capital that affects the cooperative's ability to provide loans to its members. Secondly, the lack of access to a broader market limits the sale of cooperative products. Thirdly, the insufficient involvement of the younger generation in cooperative activities threatens the sustainability of the cooperatives in the future. In addressing these challenges, several recommendations are provided. Firstly, the government needs to provide financial and technical support to cooperatives through mentoring and training programs. Secondly, cooperatives need to innovate in product marketing and expand their networks. Thirdly, cooperatives must actively engage the younger generation by involving them in decision-making processes and providing opportunities for skill development. Keywords: cooperative, economic development, challenges, and marketing